2012
DOI: 10.1002/elps.201100446
|View full text |Cite
|
Sign up to set email alerts
|

Induced‐charge electrophoresis of uncharged dielectric spherical Janus particles

Abstract: We derive the equations governing the dipolophoretic motion of an electrically inhomogeneous Janus particle composed of two hemispheres with differing permittivities. The general formulation is valid for any electric forcing, including alternating current (AC) and makes no assumptions regarding the size of the electric double layer (EDL). The solution is thus valid even for nanoparticles where the particle radius can be of the same order as the EDL thickness. Semi-analytic and numerical solutions for the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…However, it is noted that in Ref. 26 we showed that (in the limit of dc forcing) the general trends observed for the velocity in the stable configuration were the same in the case of rotation. This correlation can also be extended to the case of ac electric forcing.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…However, it is noted that in Ref. 26 we showed that (in the limit of dc forcing) the general trends observed for the velocity in the stable configuration were the same in the case of rotation. This correlation can also be extended to the case of ac electric forcing.…”
Section: Resultsmentioning
confidence: 52%
“…A rigorous derivation of the coefficients is given in Ref. 26 to yield the following two sets of coupled equations for n = 1, 2, 3. . .…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Harnett et al [37], and Wu and Li [34,35] reported that the ICEO can achieve an efficient mixing by positioning conducting triangle rods in the microchannel. Furthermore, fluid pumping [38][39][40] and particle manipulation [41][42][43] are also realizable when the ICEO flow is asymmetric.…”
Section: Introductionmentioning
confidence: 99%